2012
DOI: 10.1371/journal.pone.0050005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Myeloma Activity of Akt Inhibition Is Linked to the Activation Status of PI3K/Akt and MEK/ERK Pathway

Abstract: The PI3K/Akt/mTOR signal transduction pathway plays a central role in multiple myeloma (MM) disease progression and development of therapeutic resistance. mTORC1 inhibitors have shown limited efficacy in the clinic, largely attributed to the reactivation of Akt due to rapamycin induced mTORC2 activity. Here, we present promising anti-myeloma activity of MK-2206, a novel allosteric pan-Akt inhibitor, in MM cell lines and patient cells. MK-2206 was able to induce cytotoxicity and inhibit proliferation in all MM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 49 publications
4
61
0
Order By: Relevance
“…10,13,14). Moreover, the abnormal activation of these two pathways is associated with drug resistance and a poor prognosis of multiple myeloma (15)(16)(17). Nevertheless, previous studies have demonstrated that a sole inhibition of either the RAS/MAPK/ERK or PI3K/AKT pathways was not sufficiently efficacious to eradicate myeloma cells (10,16,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,13,14). Moreover, the abnormal activation of these two pathways is associated with drug resistance and a poor prognosis of multiple myeloma (15)(16)(17). Nevertheless, previous studies have demonstrated that a sole inhibition of either the RAS/MAPK/ERK or PI3K/AKT pathways was not sufficiently efficacious to eradicate myeloma cells (10,16,(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the abnormal activation of these two pathways is associated with drug resistance and a poor prognosis of multiple myeloma (15)(16)(17). Nevertheless, previous studies have demonstrated that a sole inhibition of either the RAS/MAPK/ERK or PI3K/AKT pathways was not sufficiently efficacious to eradicate myeloma cells (10,16,(18)(19)(20)(21). The inhibition of RAS is only effective against myeloma cells with mutated RAS, whereas the inhibition of AKT results in compensative activation of the RAS/RAF/ERK pathway in myeloma cells (16,(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, activation of the ToRC2 pathway by overexpression of DEP domain containing mTOR interacting protein (DEPTOR) 39 or activation of the ERK pathway may limit the dependency of PI3K and mToRC1. 40 The observed down-regulation of the The anti-angiogenic activity of rapalogues, via inhibition of vascular endothelial growth factor, also has to be taken into account. 42 The rate of adverse events was low in this highly pretreated group of patients suggesting that everolimus could potentially be combined with other drugs.…”
mentioning
confidence: 99%
“…were from Abcam. AZD1480 (catalog S2162) (64)(65)(66)(67)(68), ruxolitinib (catalog S1378) (69)(70)(71), perifosine (catalog S1037) (72)(73)(74)(75)(76), and MK2206 (catalog S1078) (77)(78)(79) were purchased from Selleckchem. HEK293T, MDA-MB231, T47D, DU145, and PC3 cells were purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%